Combinatorial co-expression of xanthine dehydrogenase and chaperone XdhC from Acinetobacter baumannii and Rhodobacter capsulatus and their applications in decreasing purine content in food - Chenghua Wang; Ran Zhang; Yu Sun; You Wen; Xiaoling Liu; Xinhui Xing (Food Science and Human Wellness)
This study investigated the combinatorial expression of xanthine dehydrogenase (XDH) and chaperone XdhC from Acinetobacter baumannii and Rhodobacter capsulatus and their applications in decreasing purine content in the beer, beef and yeast. Naturally occurring xdhABC gene clusters of A. baumannii CICC 10254 and R. capsulatus CGMCC 1.3366 as well as two refactored clusters constructed by exchanging their xdhC genes were overexpressed in Escherichia coli and purified to near homogeneity. RcXDH chaperoned by AbXdhC showed nearly the same catalytic performance as that by RcXdhC, except for the decreased substrate affinity. While the AbXDH co-expressed with RcXdhC displayed enhanced acidic adaptation but weakened catalytic activity. All the XDHs degraded purines in beer, beef and yeast extract effectively, indicating potential applications in low-purine foods to prevent hyperuricemia and gout. The study also presents a method for exploiting the better chaperone XdhC and novel XDHs by functional complement activity using existing XdhCs such as RcXdhC.